Meaning in Life in Menopause: A Narrative Literature Review on How Menopausal Women Make Sense of Their Life? - Anuradha Sathiyaseelan; Bishal Patangia; Pratima Hainary (Indian Journal of Psychiatric Nursing)
This review aims to understand the diverse impacts of menopause on the lives of women, with a specific emphasis on the psychological and emotional aspects, the search for meaning, the quality of life (QoL), and the personal and professional life changes that occur during this phase. Utilizing a narrative review methodology, this study employed databases such as PubMed, PsycINFO, Scopus, and Google Scholar. The criteria for inclusion encompassed articles that have undergone peer review, books, and papers presented at academic conferences that investigate the intersection of menopause, well-being, and the pursuit of meaning in life. Menopause substantially influences women’s physical well-being, mental state, and social standing. In the course of this transformative stage, women may confront a variety of psychological and emotional difficulties, encompassing depression, anxiety, and irritability, which can have detrimental consequences for their overall QoL. In addition, a woman’s perception of the significance of her life experiences undergoes alterations as she progresses through menopause. Applying efficacious coping mechanisms, such as educational initiatives regarding menopause, engagement in health-enhancing behaviors, and the availability of social support, can facilitate a more advantageous transition through this phase. Moreover, menopause presents distinctive challenges for individuals and organizations, emphasizing the significance of societal acceptance. The finding underscores the urgent requirement for enhanced psychological research, public discussion, and supportive environments to eradicate the stigma associated with menopause and foster the empowerment of women during this transformative phase.